2008
DOI: 10.1021/ma800332c
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl alcohol) Cross-Linkers for in Vivo Injectable Hydrogels

Abstract: New poly(vinyl alcohol) (PVA) derivatives containing different pendant chemoselective functionalities have been prepared for the in situ formation of hydrogels at physiological conditions. Particularly, incorporations of thiol, cysteine 1,2-aminothiol, and aminooxy side chains to PVA were performed for the first time by direct coupling of the protected nucleophilic functionalities to PVA's hydroxyl groups via carbamate linkages followed by acidic deprotection. In the second approach, PVA was first derivatized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 48 publications
1
57
0
Order By: Relevance
“…The cross-linking through Schiff base reaction between primary amine and aldehyde functional groups producing C@N double bond (Scheme S1, supplementary data) was confirmed with 13 C CP/MAS NMR spectroscopy. The solid-state NMR spectra of PVAHY, HAALD, and PVA/HA hydrogel are presented in Figure 1.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The cross-linking through Schiff base reaction between primary amine and aldehyde functional groups producing C@N double bond (Scheme S1, supplementary data) was confirmed with 13 C CP/MAS NMR spectroscopy. The solid-state NMR spectra of PVAHY, HAALD, and PVA/HA hydrogel are presented in Figure 1.…”
Section: Resultsmentioning
confidence: 71%
“…Several studies have been reported on the formation of biocompatible hydrogels from chemoselective multifunctional polymers. 12,13 This approach offers fast gelation times with a well-defined network and a possibility for injectable hydrogels. A Schiff base reaction 12 between aldehyde and amino groups of polymer derivatives is a good example, because the formation of C@N double bond is fast and does not produce any toxic by-products.…”
Section: Introductionmentioning
confidence: 99%
“…In the use of functional hydrogel for treating articular cartilage damage, suitable manufacture approaches and superb bio-materials act as important parts in developing perfect injectable polymeric hydrogels which could be considered as bio-scaffolds for bone and articular cartilage tissue engineering uses. A choice of biomedical materials, either synthetic or natural, has been elucidated to fabricate injectable polymeric hydrogels; those materials comprise poly(vinyl alcohol) [69], poly(ethylene glycol) (PEG) [70] or collagen, hyaluronic acid [71] (Figure 2, [72]), alginate [73], Advances in Materials Science and Engineeringchondroitin sulfate [74], heparin [75], gelatin [76,77] ( Figure 3, [78]), and chitosan [79]. Injectable polymeric hydrogel enables to be prepared via both chemical and physical ways.…”
Section: Different Treatments For Articular Cartilage Damage (Healingmentioning
confidence: 99%
“…Nano-scale PVA fibers have several interesting characteristics, such as high surface area to mass ratio, significant possibilities for surface functionalization, and high mechanical performance due to an improvement in the molecular organization of the spun fiber. These properties make electrospun PVA fibers excellent candidates for many applications, such as filtration, reinforcing materials, wound dressings and drug releasing carriers [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%